Trail Records and Navigational Learning. (1st November 2003) - Peterson, Don; Levene, Mark
Abstract : An emerging wave of 'ambient' technologies has the potential to support learning in new and particular ways. In this paper we propose a 'trail model' of 'navigational learning' which links some particular learning needs to the potentialities of these technologies. In this context, we outline the design and use of an 'experience recorder', a technology to support learning in museums. In terms of policy for the e-society, these proposals are relevant to the need for personalised and individualised learning support.